1981
DOI: 10.1073/pnas.78.2.1242
|View full text |Cite
|
Sign up to set email alerts
|

Net uptake of gamma-aminobutyric acid by a high-affinity system of rat brain synaptosomes.

Abstract: Rat brain synaptosomes isolated on. discontin- 'using different and more sensitive methods for measuring GABA concentration. In this paper we show that synaptosomes carry out rapid net uptake of GABA and that this net-uptake occurs through a high-affinity system. Homoexchange is shown to account for less than 10% ofthe measured [14C]GABA uptake. MATERIALS AND METHODSMale Sprague-Dawley rats (180-220 g) were used throughout the study. Synaptosomes were isolated from the forebrains of rats essentially as describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…4a. From the time courses of uptake measured at different concentrations of 13H]GABA, a K , of 6.5 pA4 and a V,,, of 400 pmoliminlmg of protein were calculated, in good agreement with values measured by other authors in rat synaptosomes (Martin, 1973;Hitzemann and Loh, 1978;Pastuszko et al, 1981). The addition of 0.5 p M p-ScTx did not modify the K , value but reduced V,,,, to 210 pmoliminimg of protein.…”
Section: P-sctx Modifies the Uptake And The Release Of [3h]gabasupporting
confidence: 84%
See 1 more Smart Citation
“…4a. From the time courses of uptake measured at different concentrations of 13H]GABA, a K , of 6.5 pA4 and a V,,, of 400 pmoliminlmg of protein were calculated, in good agreement with values measured by other authors in rat synaptosomes (Martin, 1973;Hitzemann and Loh, 1978;Pastuszko et al, 1981). The addition of 0.5 p M p-ScTx did not modify the K , value but reduced V,,,, to 210 pmoliminimg of protein.…”
Section: P-sctx Modifies the Uptake And The Release Of [3h]gabasupporting
confidence: 84%
“…It is well known that neurotoxins that activate voltage-dependent N a + channels modify the uptake and the release of neurotransmitters in synaptosomes (Blaustein, 1975). GABA, one of the primary inhibitory neurotransmitters in the mammalian CNS, is actively taken up by nerve endings (Martin, 1973;Hitzemann and Loh, 1978;Pastuszko et al, 1981), and this specific uptake is inhibited by veratridine (Blaustein and King, 1976) or a-ScTx (Romey et al, 1976). In the present study, we have confirmed that the inhibition is total with veratridine and almost total with the a-ScTx AaH 11.…”
Section: P-sctx Modifies the Uptake And The Release Of [3h]gabamentioning
confidence: 99%
“…These results were based on the observation that external GABA promotes the release of [3H]GABA (Levi and Raiteri, 1978). However, this is due to exchange rather than net efflux ; indeed, on addition of external GABA, there is a net uptake of HPLC-detected GABA, rather than a release (Roskoski, 1978;Pastuszko et al, 1981). Figure 2A illustrates the distinctive kinetics of KCIinduced L-glutamate release from synaptosomes by Ca2+-dependent and -independent mechanisms as monitored by continuous fluorometric assay.…”
Section: Plasma Membrane Amino Acid Transport and The Nature Of Caz+-mentioning
confidence: 99%
“…In order to fulfill these functions, these nerve terminal transport systems must be able to mediate net transmitter uptake. Indeed, Roskoski (1978; and see Ryan & Roskoski, 1977;Pastuszko, Wilson & Erecinska, 1981) has shown that synaptosomes can engage in net accumulation of 7-aminobutyric acid (GABA) and L-glutamate.…”
Section: Introductionmentioning
confidence: 98%